Metode Pengajaran Dalam QS. An-Nahl (16) : 125 - Mazro’atus Sa’adah (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2016)
This article discusses the teaching methods in the QS. An-Nahl (16): 125 (study of tafseer). As we know that the success of a teaching depends on the method used to deliver it. In the QS. An-Nahl (16): 125 is explained there are three ways of preaching (teaching) that are tailored to the subject being taught, namely wisdom, mau'idhoh hasanah, and jidal. Interpretation of the study stated that the way of preaching (teaching) with wisdom intended for people who already have knowledge (scholars) that dialogue with the wise words according to their skill level, how to preach (teaching) with mau'idhoh hasanah intended for the general public by providing advice that is simple, while the means of preaching (teaching) with jidal used for highly educated people who have mastered the various sciences and being able to argue with the right arguments, separated from the fine rhetoric of violence and expletives. That ways if related by education, in presenting the material, the teacher should pay attention to the ability of the students, whether the student is suitable if the material is conveyed only by his lectures alone or listening to a story, or students able to be consulted in ways that better? It is important for teachers to material success conveys.